Drug-Herb Interactions among Thai Herbs and Anticancer Drugs: A Scoping Review - Apisada Jiso; Phisit Khemawoot; Pinnakarn Techapichetvanich; Sutinee Soopairin; Kittiphong Phoemsap; Panrawee Damrongsakul; Supakit Wongwiwatthananukit; Pornpun Vivithanaporn (MDPI AG, 2022)
More than half of Thai patients with cancer take herbal preparations while receiving anticancer therapy. There is no systematic or scoping review on interactions between anticancer drugs and Thai herbs, although several research articles have that Thai herbs inhibit cytochrome P450 (CYP) or efflux transporter. Therefore, we gathered and integrated information related to the interactions between anticancer drugs and Thai herbs. Fifty-two anticancer drugs from the 2020 Thailand National List of Essential Medicines and 75 herbs from the 2020 Thai Herbal Pharmacopoeia were selected to determine potential anticancer drug-herb interactions. The pharmacological profiles of the selected anticancer drugs were reviewed and matched with the herbal pharmacological activities to determine possible interactions. A large number of potential anticancer drug-herb interactions were found; the majority involved CYP inhibition. Efflux transporter inhibition and enzyme induction were also found, which could interfere with the pharmacokinetic profiles of anticancer drugs. However, there is limited knowledge on the pharmacodynamic interactions between anticancer drugs and Thai herbs. Therefore, further research is warranted. Information regarding interactions between anticancer drugs and Thai herbs should provide as a useful resource to healthcare professionals in daily practice. It could enable the prediction of possible anticancer drug-herb interactions and could be used to optimize cancer therapy outcomes.